Vancomycin-Stabilized Platinum Nanoparticles with Oxidase-like Activity for Sensitive Dopamine Detection - Yuzhen Xue; Kai Liu; Mingyue Gao; Tiantian Zhang; Longgang Wang; Yanshuai Cui; Xianbing Ji; Guanglong Ma; Jie Hu (Biomolecules, 2023)
The development of efficient, reliable, and sensitive dopamine detection methods has attracted much attention. In this paper, vancomycin-stabilized platinum nanoparticles (Van-Ptn NPs, n = 0.5, 1, 2) were prepared by the biological template method, where n represented the molar ratio of vancomycin to Pt. The results show that Van-Pt2 NPs had oxidase-like activity and peroxidase-like activity, and the mechanism was due to the generation of reactive oxygen 1O2 and OH. Van-Pt2 NPs exhibited good temperature stability, storage stability, and salt solution stability. Furthermore, Van-Pt2 NPs had almost no cytotoxicity to A549 cells. More importantly, the colorimetric detection of DA in human serum samples was performed based on the oxidase-like activity of Van-Pt2 NPs. The linear range of DA detection was 10–700 μM, and the detection limit was 0.854 μM. This study establishes a rapid and reliable method for the detection of dopamine and extends the application of biosynthetic nanoparticles in the field of biosensing.